Agritourism Enhancing Small Farm Operations: A Research Model - McClanahan, Lauren E.; Wilson, Asa B. (Archives of Business Research, 2023)
Challenges confronting small- and mid-size farm operations are identified in terms of risks to sustainability. Community, economic, and environmental factors supporting sustainable farm operations are outlined. Incorporating and/or expanding agritourism activities are discussed as interventions supporting sustainability. Uncertainty about agritourism features that enhance farm operations is problematic. A university-based agritourism pilot study with small- and medium-sized farm in rural southeast Missouri provided insight into a needed follow-up research model. This research approach is defined in terms of its agritourism a) background, b) research question, c) methodology, d) data source, e) statistical analysis, and f) applied value. The applied value of research findings impacts academic understanding of agritourism, provides guidance for individual farm operators, and fosters wide scope agritourism research opportunities in regions, states, multiple counties, and other defined geographies.